2018
DOI: 10.1038/s41598-018-19278-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological status of plant tissue affects the frequency and types of mutations induced by carbon-ion irradiation in Arabidopsis

Abstract: Ionizing radiation including heavy-ion beams has been widely used in mutation breeding. Dry seeds, seedlings, and cultured tissues are often used for mutagenesis; however, little is known about the differences in induced mutations among them. Here, we examined the characteristics of mutations using randomly chosen Arabidopsis M2 plants derived from dry seeds and seedlings irradiated with carbon ions. The mutation frequency was 1.4–1.9 times higher in dry-seed irradiation than in seedling irradiation. This diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
73
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 24 publications
6
73
2
Order By: Relevance
“…The average number of mutated genes, including both homozygous and heterozygous mutations, was 13 in each M 3 mutant (Kazama et al ., ; Du et al ., ). In the case of randomly chosen M 2 lines, an average of 7.0 genes were affected as homozygous mutations (Hase et al ., ). In addition, relatively large deletions and genomic rearrangements, such as inversions and translocations, were also detected by WGS of selected carbon‐ion irradiation‐derived mutants.…”
Section: Introductionmentioning
confidence: 97%
“…The average number of mutated genes, including both homozygous and heterozygous mutations, was 13 in each M 3 mutant (Kazama et al ., ; Du et al ., ). In the case of randomly chosen M 2 lines, an average of 7.0 genes were affected as homozygous mutations (Hase et al ., ). In addition, relatively large deletions and genomic rearrangements, such as inversions and translocations, were also detected by WGS of selected carbon‐ion irradiation‐derived mutants.…”
Section: Introductionmentioning
confidence: 97%
“…The characterization of the molecular nature of mutations is important for the efficient use of different types of mutagen treatments. Recent advances in high-throughput sequencing technologies have greatly accelerated the understanding of the molecular nature of mutations, particularly those induced by high-LET radiation (Belfield et al, 2012;Hirano et al, 2015;Du et al, 2017;Kazama et al, 2017;Hase et al, 2018;Ichida et al, 2019;Jo and Kim, 2019). An extensive analysis in Arabidopsis suggested that ion beams with very high LET values induce drastic and complex alterations of chromosomes, while ion beams with moderate LET values often induce short insertions and deletions (InDels).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of the latter is preferable to achieve a high frequency of loss-of-function mutations (Kazama et al, 2017). We previously compared the mutations induced by carbon ion irradiation of Arabidopsis dry seeds and seedlings, and we demonstrated that the tissue type greatly affected the frequency and types of mutations (Hase et al, 2018). A neutron is also a kind of high-LET radiation, and a large-scale mutant population having a mutation database determined by whole-genome resequencing was constructed in the model rice cultivar Kitaake (Li et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend was observed in the presence of homopolymers or polynucleotide repeats at flanking sequences of small InDels in the genome of carbon ion-beam-irradiated Arabidopsis [18,20]. Hase et al [34] inferred that distinct mechanisms are involved in between the generation of the single base deletion and larger-sized deletions in carbon ion-irradiated Arabidopsis. They also suggested that much larger size deletions (≧ 50 bp) are generated via another distinct mechanism.…”
mentioning
confidence: 62%